THE EFFECTIVENESS OF INSTAGRAM SOCIAL MEDIA MARKETING IN INCREASING BRAND AWARENESS OF THE INTEGRATED STATISTICS SERVICE OF BPS-STATISTICS TANGERANG REGENCY - Reza Septian Pradana (CV. Radja Publika, 2026)
The low utilization of the Integrated Statistics Service (PST) of BPS-Statistics Tangerang Regency indicates a problem in the level of public brand awareness, even though the quality of service is classified as very good, so a more effective communication strategy is needed through social media marketing, especially Instagram. This study aims to analyze the effectiveness of utilizing Instagram in increasing brand awareness of the PST BPS Tangerang Regency using a qualitative method through a case study approach, where data is collected through social media analytics-based observations and in-depth interviews with three internal sources, and analyzed comparatively between conditions in 2023 and 2024. The results of the study show a significant increase in the number and quality of Instagram content in 2024 compared to 2023, although the proportion of content specifically containing PST information is still relatively limited; however, the increase in audience interaction, the number of followers, and the increase in offline service users indicate that social media marketing through Instagram is effective in increasing brand awareness to reach the level of brand recognition and brand recall in the general public as well as brand dominance in the local government segment. The decline in online service users does not entirely reflect Instagram's ineffectiveness, but is influenced by external factors such as user behavior that does not follow service procedures, so strategy optimization is needed through increasing content variety and intensity, delivering more comprehensive service information, utilizing interactive features such as reels, and integrating email marketing to significantly increase engagement, loyalty, and conversion of service usage.